Testing for a time-varying price-cost markup in the Euro area inflation process. - Bowdler, C; Jansen, E (Nuffield College (University of Oxford), 2004)
Empirical models of inflation often incorporate equilibrium correction effects based upon levels of prices and input costs. Such models assume that the steady-state price-cost markup is constant, but recent research suggests that this may not be true for the Euro area economy, which has undergone major structural reforms over the last 25 years. We allow for permanent shifts in the markup factor through estimating an inflation equation that includes a time-varying intercept. The model suggests that a reduction in the markup contributed to disinflation in the Euro area during the period 1981-2000.